Al-Ṣūratu al-Bayyāniyatu fī Qaṣidati Ṭalabatka Yā Dundā liabī al-‘Atāhiyati - Aminor, Aminor; Sudiarti, Sri; Ritonga, Ridwan (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
As-Shurah Al-Bayaniyyah: is the expression of the intended meaning through simile, metaphor, metaphor, metonymy, or embodiment of meanings. The purpose of this research is to know the verses in the poem “I asked you, oh world,” which include the graphic image and the linguistic and graphical explanation of the poem. The type of research used is qualitative research. The source of the research data is the poem I asked for you, Ya Dunya, by Abu Al-Atahiya. The method used to analyze data is a description of the analysis. The results of the research are that the number of graphic images in the poem “I asked you, O world” by Abu Al-Atahiya is nineteen graphic images. The number of simile in the poem is four, the number of metaphor in the poem is eight, and the number of metonymy in the poem is seven.